The artist as a political vandal and moral witness: Lucienne Rickard’s Extinction Studies - Billy Badger (Journal of Aesthetics & Culture, 2025)
Extinction Studies was a years-long, politically motivated artistic event that blurs the boundaries not only between traditional “conservable” visual artwork and ephemeral performance but also between scientific rigour and emotional truth-telling. In the long chronology of art history, Lucienne Rickard’s Extinction Studies project is by no means the first artistic engagement with modes of destruction in any of art’s key domains. Yet, Rickard’s interplay between destruction of art, as art, and in art represents a unique opportunity for the Tasmanian visual artist to assert effective political agency. In the following, I investigate the characteristics of Extinction Studies that justify the twin appellations of political art and ideological vandalism as the testimony of a moral witness to what is commonly referred to as the sixth mass extinction.